The Conflicting Synthesis of the Taliban’s Religious and Cultural Identity - Zaland, Faiz Muhammad (The review of faith & international affairs, 2023)
Though there is no constitution or founding document at present, a book written in 2022 by Abdul Hakim Haqqani, the Chief Justice of the Taliban’s government, titled The Islamic Emirate and Its System (al-Imarat al-Islamiat wa-Manzumatuha) appears to be a blueprint for the newly minted Islamic Emirate (IEA). This is the first intentionally prepared written source by a senior Taliban official on the intellectual foundations of the IEA structure. The book addresses various subjects, such as the sources of Islamic legislation, independence, and the principles of politics, judiciary, and economics. It is a distillation of the intellectual foundations, and it offers new insight into the Taliban's political strategy. In this essay I present some of the central ideas of Haqqani’s book and question its implications for understanding the conflicting synthesis of the Taliban’s religious and cultural identity.